Design Of Battery Storage System For Malaysia Low Voltage Distribution Network With The Presence Of Residential Solar Photovoltaic System - Gan, Chin Kim; Shamshiri, Meysam; Sardi, Junainah; Mau, Teng Au; Wei, Hown Tee (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The recent proliferation of residential solar photovoltaic systems has prompted several technical challenges to the operation of low voltage (LV) distribution networks. More specifically, the mismatch of the solar generation and demand profiles, particularly during the midday when the demand is low and solar generation is high, can lead to network overvoltages and increased network losses. In addition, the solar photovoltaic system is not able to reduce the system’s maximum demand, given the residential LV network would normally have an evening peak when the sun goes down. In this regard, this paper examines two different control strategies in designing the battery energy storage system. One aims to eliminate reverse flow caused by the surplus solar energy and the other aims for peak demand reduction